INVOICE LETTERS - Feby Feby; Desi Ratna Sari (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2022)
This article aims to provide readers with information about invoice letters. This article can help learning, especially for business management majors in learning English in each of these courses. For those who already know, hopefully they can understand better, for those who haven't expected it will be useful additional knowledge. This article is a library research, the writer collect some sources about invoice and investigate some documents from companies. This article generally discusses business letters, but what is more emphasized here is about invoices. Many people are still confused about what an invoice is, where we can find an invoice and what it is used for. Therefore, this article discusses this problem. Keywords: Invoice Letters, Business Letters